Analyzing the discourse surrounding Autism in the New York Times using an ableism lens - Billawala, Alshaba; Wolbring, Gregor (Disability Studies Quarterly, 2014)
The topic of Autism is highly within academic literature (over 20000 articles in the database PubMed of US National Library of Medicine, National Institutes of Health and the public domain (79 Million hits in Google). Newspapers also show a great interest in autism. However despite the prevalence of autism coverage very little media analysis has been performed. We present here an analysis of the coverage of autism in the New York Times from the time the term autism first appeared (1973) to 2012. Ability expectations and preferences are one dynamic through which members of a group judge others, themselves and their lives. Ability preferences and judgments are at the root of many rules of behaviours and customs. Ableism was one lens through which we analyzed the discourse surrounding autism in the NYT. We found that readers that rely on the NYT as a primary source of information get very limited information about what autism is and what factors are associated with autism and they are heavily exposed to a medical narrative. We suggest that the negative, medical narrative adds to the problems people with autism face. Keywords: autism; perception; media; New York Times; language; ableism